2009
DOI: 10.3382/ps.2007-00440
|View full text |Cite
|
Sign up to set email alerts
|

Islet-derived stellate-like cells as a novel source for islet neogenesis in chicks

Abstract: The therapeutic potential of stem cells has led to renewed interest in regenerative biology. Pancreatic stellate cells have been reported in the mammalian pancreas; however, there are very few reports on stellate cells in the chicken pancreas. The intercalated duct epithelial cells observed in the A and B islets of the chicken pancreas have been claimed to be stellate cells from their morphological appearance. While isolating islets and acinar cells from the chick pancreas, we have found a population of stella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…3,4 However, more recent studies have described α-SMA positive cells, identified as PSCs, in the islets of humans with T2DM and in animal models. 16,[20][21][22] In the current study we identify an α-SMA positive population of stellate cells within isolated islets which are similar, but not identical to classical PSCs, and which we have called islet stellate cells. In view of the central role of PSCs in pancreatic fibrosis, we suggest that ISCs may contribute to the islet fibrosis in the development of T2DM.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…3,4 However, more recent studies have described α-SMA positive cells, identified as PSCs, in the islets of humans with T2DM and in animal models. 16,[20][21][22] In the current study we identify an α-SMA positive population of stellate cells within isolated islets which are similar, but not identical to classical PSCs, and which we have called islet stellate cells. In view of the central role of PSCs in pancreatic fibrosis, we suggest that ISCs may contribute to the islet fibrosis in the development of T2DM.…”
Section: Introductionmentioning
confidence: 69%
“…But chick ISCs showed spontaneous adipogenesis after 2nd and 3rd passages, which was different in rat ISCs. 22 The diabetic environment provides numerous signals which could lead to stellate cell activation. Thus, previous studies using classical PSCs have demonstrated that hyperglycemia, 16,31 activation of the RAS, 32 oxidative stress, 17,30 platelet-derived growth factors, 33 and inflammatory cytokines 34 all enhance PSC activation and proliferation.…”
Section: -1227mentioning
confidence: 99%
“…Nestin and vimentin are markers of stellate cells and mesenchymal cells (Datar and Bhonde, 2009;Lardon et al, 2002;Omary et al, 2004Omary et al, , 2007. We found the distribution of nestin-positive cells and vimentin-positive cells in the interstitial tissues of pancreas.…”
Section: Discussionmentioning
confidence: 83%
“…PSCs from rat and human pancreata have demonstrated their self-renewal and differentiation capacity and give rise to all three germ layers ectoderm, endoderm and mesoderm. 52 In similar lines, studies by Datar and Bhonde et al 53 reported for the first time the presence of a stellate-like cell population in chick pancreatic islets, suggesting stellate cells could form a new source for islet neogenesis. Further, establishment of chick PSC culture would provide an alternative model for testing factors having mitogenic and islet neogenic properties.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 76%